Periodicities in the K2 light curve of HP Librae. Issue 1 (20th October 2020) - Solanki, Siddhant; Kupfer, Thomas; Blaes, Omer; Breedt, Elmé; Scaringi, Simone
ABSTRACT: We analyse Kepler/K2 light-curve data of the AM CVn system HP Librae (HP Lib). We detect with confidence four photometric periodicities in the system: the orbital frequency, both positive and negative superhumps, and the positive apsidal precession frequency of the accretion disc. This is only the second time that the apsidal precession frequency has ever been directly detected in the photometry of a helium accreting system, after SDSS J135154.46-064309.0. We present phase-folded light curves and sliding power spectra of each of the four periodicities. We measure rates of change of the positive superhump period of ∼10 −7  d. We also redetect a quasi-periodic oscillation (QPO) at ∼300 cyc d –1, a feature that has been stable over decades, and show that it is harmonically related to two other QPOs, the lowest of which is centred on the superhump/orbital frequency. The continuum power spectrum is consistent with a single power law with no evidence of any breaks within our observed frequency range.